2015
DOI: 10.1007/s10549-014-3175-4
|View full text |Cite
|
Sign up to set email alerts
|

A polygenic risk score for breast cancer in women receiving tamoxifen or raloxifene on NSABP P-1 and P-2

Abstract: Recent genetic studies have identified common variation in susceptibility loci that stratify lifetime risks of breast cancer and may inform prevention and screening strategies. However, whether these loci have similar implications for women treated with tamoxifen or raloxifene (SERMs) is unknown. We conducted a matched case–control study of 592 cases who developed breast cancer and 1,171 unaffected women from 32,859 participants on SERM therapy enrolled on NSABP P-1 and P-2 breast cancer prevention trials. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…One promising area of study involves using the PRS to identify women who would benefit from chemoprevention, since it is unknown whether a high PRS is predictive of benefit from tamoxifen. Although the PRS has been assessed in high-risk women enrolled in two large tamoxifen prevention trials [47], there are no comparative data on the PRS in women who received placebo, and the relative benefit of tamoxifen in women with high polygenic risk remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…One promising area of study involves using the PRS to identify women who would benefit from chemoprevention, since it is unknown whether a high PRS is predictive of benefit from tamoxifen. Although the PRS has been assessed in high-risk women enrolled in two large tamoxifen prevention trials [47], there are no comparative data on the PRS in women who received placebo, and the relative benefit of tamoxifen in women with high polygenic risk remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the SNP score provided useful additional information not contained in the TC model, but the overall prediction was somewhat optimistic and calibration was poor. This was also seen for another polygenic risk score in a case-control study of women from two other prevention trials [ 7 ]. However, other studies have not seen a loss in calibration (8, van Veen et al submitted).…”
mentioning
confidence: 53%
“…In addition, breast cancer risk models and SNP based risk stratification could also be focused on ER-positive breast cancer. However, since most breast tumors are ER-positive, SNP-based models designed for overall breast cancer perform well for ER-positive breast cancer[41]. Another assumption behind our approach is that the women who are identified as high risk by SNPs will be protected from breast cancer by chemoprevention to the same degree that women who were included in the breast cancer prevention trials.…”
Section: Discussionmentioning
confidence: 99%
“…Another assumption behind our approach is that the women who are identified as high risk by SNPs will be protected from breast cancer by chemoprevention to the same degree that women who were included in the breast cancer prevention trials. Recent data from breast cancer prevention trials re-analyzed to include SNP-based risk, suggests that SNPs can be used to find women who would benefit from chemoprevention with SERMs[41]. If women identified as high risk based on SNPs have an intrinsically different response to preventive treatments, the risk/benefits would need to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%